Selenium regulates transcription factor NF-κB activation during the acute phase reaction - Maehira, Fusako; Miyagi, Ikuko; Eguchi, Yukinori (Clinica chimica acta, 2003)
Background: We reported a reciprocal relationship between reduced serum selenium (Se) and elevated serum C-reactive protein (CRP) in various pathological conditions in comparison with the levels in 141 healthy subjects. To clarify the implications of these observations, the effect of Se on nuclear factor (NF)-κB, which upregulates the CRP synthesis in the liver, was examined. Methods: Human hepatoma cell line HuH-7 was cultured in medium with 2% fetal calf serum (FCS) for 3 days for the Se deprivation, followed by another 3 days in the same medium containing sodium selenite prior to stimulation of the cells with either monocyte-conditioned medium (MoCM) or tumor necrosis factor-α (TNF-α). NF-κB activation and the synthesis of CRP in hepatocytes were examined by a non-radioisotope (non-RI) gel shift assay for the nuclear extract from the cells and by a highly sensitive ELISA for the cellular extract, respectively. Results: The NF-κB activation induced by MoCM and TNF-α were inhibited by Se at the physiological levels. The maximum activation of NF-κB was induced by TNF-α or MoCM at a Se concentration (0.5∼1 μmol/l) which was half the level of the serum Se in healthy subjects and was equivalent to level in subjects with pathological conditions together with high serum CRP values. Under the same conditions, the hepatocytes synthesized maximal amounts of CRP. Conclusions: Selenium at physiological levels mediates inhibition of the activation of the transcription factor NF-κB which regulates genes that encode inflammatory cytokines, and that conversely, the reduction of selenium induces the synthesis of CRP by hepatocytes during the acute phase response.